Adjuvant transarterial chemoembolization improves survival outcomes in hepatocellular carcinoma with microvascular invasion: A systematic review and meta-analysis. Issue 11 (November 2019) - Chen, Zhen-Hua; Zhang, Xiu-Ping; Zhou, Teng-Fei; Wang, Kang; Wang, Hang; Chai, Zong-Tao; Shi, Jie; Guo, Wei-Xing; Cheng, Shu-Qun
Abstract: Background: The benefits of adjuvant transarterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI) remain controversial. We compared the efficacy and safety of adjuvant TACE and hepatic resection (HR) alone for HCC patients with MVI. Methods: The PubMed, EMBASE, Cochrane Library, VIP, Wan Fang, and Sino Med databases were systematically searched to compare adjuvant TACE and HR alone for the treatment of HCC with MVI from inception to January 1, 2019. The study outcomes, including overall survival (OS) and disease-free survival (DFS), were extracted independently by two authors. Results: 12 trials involving 2190 patients were evaluated. A meta-analysis of 11 studies suggested that the 1-, 3-, and 5-year overall survival (OS) rates (OR = 0.33, P < 0.001; OR = 0.49, P < 0.001; and OR = 0.59, P < 0.01; respectively), favored adjuvant TACE over HR alone. 11 studies were included in the meta-analysis of DFS, and adjuvant TACE showed better 1-, 3-, and 5-DFS (OR = 0.45, P < 0.001; OR = 0.50, P < 0.001; and OR = 0.58, P < 0.001; respectively) compared to HR alone. Subgroup analysis demonstrated that adjuvant TACE could benefit HCC patients with MVI with tumor diameter >5 cm or multinodular tumors. Conclusion: Adjuvant TACE may improve OS and DFS for HCC patients with MVI compared to HR alone and should be recommended for selected HCC patients with MVI. However, these results need to be validated through further high-quality clinical studies. Lay summary: The benefits of adjuvant TACE in HCC patients with microvascular invasion remain controversial. Twelve studies involving 2190 patients were include in our meta-analysis. Adjuvant TACE may improve OS and DFS for HCC patients with MVI compared to HR alone and should be recommended for selected HCC patients with MVI.